Awareness of Ethical and Medico-Legal Issues Among Medical Professionals of a Private Institute (Indian Internet Journal of Forensic Medicine and Toxicology, 2015)
Background: Medical council of India has laid down certain guidelines for the medical professionals to follow. Being an integral part of medical practice, it is mandatory for medical professionals to have knowledge of medical ethics. This study was undertaken to assess the awareness of ethical and medico-legal issues among medical professionals of a private institute. Material and methods: It was a cross-sectional, questionnaire-based study carried out in 134 medical professionals using a structured and validated questionnaire. The data was analysed using EPI-Info statistical software version 6 for number and percentage. Results: We observed that 86.6% participants were aware about code of medical ethics and its importance in medical profession, they acquired the knowledge of medical ethics as experience at work (58.2%) followed by lectures and seminar (26.1%), 95.5% were aware about the different types of consent and its importance in medical profession, 85.1% were aware about medico-legal cases and 56.7% participants stated that proper documentation and consent can prevent a charge of negligence. Conclusion: To conclude with, though participants were aware about basic facts of ethical and medico-legal issues, various finer aspects need to boost up time to time to avoid future legal actions.
Keywords: Medical ethics; Medical professionals; Medico-legal issues; Medico-legal cases; Consent; Doctor-patient relationship; Medical indemnity insurance